2019
DOI: 10.1002/pd.5476
|View full text |Cite
|
Sign up to set email alerts
|

High risk—What's next? A survey study on decisional conflict, regret, and satisfaction among high‐risk pregnant women making choices about further prenatal testing for fetal aneuploidy

Abstract: Objectives:To investigate decision making among pregnant women when choosing between noninvasive prenatal testing, invasive testing, or no further testing. Methods:Women with a high-risk result from the first trimester screening were invited to fill in two online questionnaires at gestational age 12 to 14 (Q1) and 24 weeks (Q2). The scales used were Decisional Conflict and Regret Scales, Satisfaction with genetic Counselling Scale, and Health-Relevant Personality Inventory.Results: Three hundred thirty-nine wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 19 publications
4
25
0
Order By: Relevance
“…Denmark has comprehensive and free of charge prenatal care available to all pregnant women including a combined first‐trimester screening and a second‐trimester malformation scan . In case of a high‐risk screening result, women are offered a choice between non‐invasive prenatal testing and invasive diagnostics, and the majority choose the latter . In case of detected or suspected fetal anomaly, women are offered invasive diagnostics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Denmark has comprehensive and free of charge prenatal care available to all pregnant women including a combined first‐trimester screening and a second‐trimester malformation scan . In case of a high‐risk screening result, women are offered a choice between non‐invasive prenatal testing and invasive diagnostics, and the majority choose the latter . In case of detected or suspected fetal anomaly, women are offered invasive diagnostics.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that pregnant women who enter into prenatal screening and testing often request maximum information about their unborn child, including uncertain CNV results . However, they may be unprepared for the scope and complexity of such information, and for the reproductive decisions that the new situation entails.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty in the prenatal setting is particularly challenging because many parents enter into prenatal testing hoping for reassurance of a healthy baby (Lou et al, 2017;Oyen & Aune, 2016). Studies have found that pregnant women often want maximal information about their unborn child (Hartwig, Miltoft, Malmgren, Tabor, & Jørgensen, 2019;van der Steen et al, 2015;Walser et al, 2015), but may be unprepared for the scope and complexity of such information (Bernhardt et al, 2013;Riedijk et al, 2014). The difficulty in robustly correlating VUS results with phenotypic outcomes, or in predicting how affected a child will be by an SL result, complicate both understanding and decision-making for couples trying to decide what the results mean to them and what the consequences should be (Riedijk et al, 2014;Rubel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another Danish study, this in a high-risk population demonstrated that 75% of women chose an invasive test and 24% chose cfDNA testing. Choosing cfDNA was found to be associated with a high decisional conflict and therefore lower satisfaction with the genetic counseling was associated with low decisional conflict and later decisional regret (Hartwig et al, 2019). In Sweden, a divided attitude toward invasive testing was found in high school students because 29% of them showed uncertainty about this method, while 48% had a very positive attitude toward it (Georgsson et al, 2017).…”
Section: Comparison With the Literaturementioning
confidence: 99%